Effect of Sodium Alginate Concentration on Characteristics, Stability and Drug Release of Inhalation Quercetin Microspheres - Tekla Kalalo; Andang Miatmoko; Hanafi Tanojo; Tristiana Erawati; Dewi Melani Hariyadi; Noorma Rosita (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Quercetin is a flavonoid compound that has anti-inflammation activity. However, poor stability presents significant problems for the formulation into dosage forms. Microspheres are one of the potential lung delivery systems because of their ability to encapsulate various types of drugs, protect drugs from environmental effects and can release drugs in a sustained release. Objective: In the present study, the microsphere inhalation system of the anti-inflammation drug, quercetin was developed and evaluated to achieving the targeted delivery of these drugs to the lung. Method: The drug-loaded ca-alginate microspheres were prepared by aerosolization ionic gelation technique followed by freeze-drying. Result: The result of this study showed that particle size was less than 2 µm, the yield ranged from 41.33-76.14%, drug loading was less than 6%, entrapment efficiency ranged from 74.153% - 93.805% and flow properties showed that all formula had an excellent flow. Spherical microspheres were demonstrated by formulations containing 1 and 1.5% sodium alginate. A drug release study showed that the highest drug release of 30.649% was from the formulation with 2.5% sodium alginate, and the lowest drug release of 26.625% was from the formulation with 2% sodium alginate. , A stability study at temperatures of 25áµ’C and 40áµ’C for 28 days showed a decrease in drug loading and entrapment efficiency but an increase in particle size. The formulation containing 1.5% sodium alginate showed the optimal formula. Conclusion: These findings indicated that quercetin ca-alginate microspheres are the potential for inhalation to be delivered to the lung.